2014
DOI: 10.1007/s10151-014-1207-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporary sacral neuromodulation under local anaesthesia using new anatomical reference points

Abstract: Temporary sacral neuromodulation can be reliably performed in a more practical, less expensive outpatient setting under local anaesthesia without adversely influencing test outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…the remaining patients had replacement of the lead alone. in assessing the baseline characteristics of each group, the median CCf-fis was found to be significantly higher preoperatively in the reimplantation group as compared with the index implantation controls (index implantation: 17 (range, [8][9][10][11][12][13][14][15][16][17][18][19][20]; reimplantation: 19 (range, [12][13][14][15][16][17][18][19][20]; p = 0.002). in addition, the postoperative median CCf-fis was found to be significantly higher in the reimplantation group (index implantation: 7 (range, 0-20); reimplantation: 12 (range, 3-20) p = 0.028).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the remaining patients had replacement of the lead alone. in assessing the baseline characteristics of each group, the median CCf-fis was found to be significantly higher preoperatively in the reimplantation group as compared with the index implantation controls (index implantation: 17 (range, [8][9][10][11][12][13][14][15][16][17][18][19][20]; reimplantation: 19 (range, [12][13][14][15][16][17][18][19][20]; p = 0.002). in addition, the postoperative median CCf-fis was found to be significantly higher in the reimplantation group (index implantation: 7 (range, 0-20); reimplantation: 12 (range, 3-20) p = 0.028).…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] Briefly, during stage 1, patients are placed in the prone position and monitored anesthesia care is performed with conscious sedation. after the use of local anesthesia, anatomical landmarks are recognized and marked.…”
Section: Study Populationmentioning
confidence: 99%
“…Characteristics of the 49 included patients are shown in Table 2. The median duration of the interval between the preoperative and postoperative mailing and the SNM was 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) months.…”
Section: Resultsmentioning
confidence: 99%
“…Our operative technique for temporary and permanent SNM under local anaesthesia has been previously described [13,14]. All patients in our institution underwent a percutaneous nerve evaluation (PNE) using a temporary test stimulation lead (Medtronic model 3057 test stimulation lead).…”
Section: Methodsmentioning
confidence: 99%
“…When the procedure is performed under local anaesthesia this gives the added bonus of patient feedback regarding sensory responses that confirm the correct positioning of the lead and help select the appropriate foramen. [6,7] Isolated sensory responses don't necessarily mean that permanent implantation will fail. Cohen et al reported that motoric responses are superior to sensory responses in predicting clinical success so they recommend to perform permanent implantation solely when motoric responses were elicited.…”
Section: The Value Of Sensory Responsesmentioning
confidence: 99%